Advances in the development of molecular genetic tools for Mycobacterium tuberculosis. (20th June 2018) - Chhotaray, Chiranjibi; Tan, Yaoju; Mugweru, Julius; Islam, Md Mahmudul; Adnan Hameed, H.M.; Wang, Shuai; Lu, Zhili; Wang, Changwei; Li, Xinjie; Tan, Shouyong; Liu, Jianxiong; Zhang, Tianyu
Abstract: Mycobacterium tuberculosis, a Gram-positive bacterium of great clinical relevance, is a lethal pathogen owing to its complex physiological characteristics and development of drug resistance. Several molecular genetic tools have been developed in the past few decades to study this microorganism. These tools have been instrumental in understanding how M. tuberculosis became a successful pathogen. Advanced molecular genetic tools have played a significant role in exploring the complex pathways involved in M. tuberculosis pathogenesis. Here, we review various molecular genetic tools used in the study of M. tuberculosis. Further, we discuss the applications of clustered regularly interspaced short palindromic repeat interference (CRISPRi), a novel technology recently applied in M. tuberculosis research to study target gene functions. Finally, prospective outcomes of the applications of molecular techniques in the field of M. tuberculosis genetic research are also discussed.